MENGGALI ESENSI FALSAFAH KESATUAN ILMU DALAM PERSPEKTIF FILOSOFIS - Ainur Rosyadah; Nita Yulia Astuti; Maftukhah Lailatul Urbah (EL-ADABI : Jurnal Studi Islam, 2025)
This article examines the philosophy of the unity of knowledge from a philosophical perspective, emphasizing the understanding of knowledge as an integrated whole that combines reason, morality, and spirituality. Modern scientific development tends toward fragmentation into isolated disciplines, exacerbated by a positivist paradigm that prioritizes technical and economic aspects while neglecting moral and spiritual values. Through a literature study, this article reflects on the concept of the unity of knowledge as formulated in the Islamic intellectual tradition by figures such as Al-Farabi, Ibn Sina, Al-Ghazali, and Ismail Raji al-Faruqi, offering a philosophical approach to bridging science, values, and the meaning of life. Interdisciplinary integration is viewed as an essential strategy to address social, cultural, and ethical challenges in the era of globalization. The article asserts that the unity of knowledge is not merely an idealistic notion but a fundamental necessity in building a civilized, just, and sustainable society, enabling knowledge to serve both as a means of empowerment and a guide toward a dignified life.